A case of skin lesions of basal cell nevus syndrome - Chen, Long; Sun, Hui; Zuo, Meng; Xi, Qing (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Basal cell nevus syndrome (BCNS) is a rare autosomal dominant disorder, and is believed to be caused by mutations in the PTCH gene at locus 9Q22.3-Q31. It is a complex syndrome and consists of multiple odontogenic keratocysts, multiple basal cell nevus (cancer) of the face and neck, punctate depression of the palm and sole, abnormal skeleton and rib, calcification in the brain and various other defects [1, 2]. Now we are reporting a case of BCNS seen in our department recently as follows: female, 20 years old, with typical clinical manifestations of BCNS: multiple and scattered pigmented nevus on the face (Figure 1 A), small depression on the palm (Figure 1 B), multiple cysts on the upper and lower jaw, calcification of cerebral falx and tentorium, sternum deformity, rib bifurcations, scoliosis, deviation of the right eye with decreased vision. The mother presented with multiple cysts of the upper and lower jaws, bifurcated ribs, scoliosis and scattered small depressions in the palm (Figure 2).